Pengaruh Teknik Guided Imagery Terhadap Perubahan Nyeri pada Pasien Post Operasi Abdomen di Ruang Plamboyan RSUD Praya Kabupaten Lombok Tengah - Sarifudin (Journal of Nursing Perspectives, 2025)
Postoperative pain is a common problem experienced by patients after abdominal surgery and may negatively affect recovery, mobility, and overall quality of life, making effective pain management an essential component of nursing care. In addition to pharmacological therapy, non-pharmacological interventions such as guided imagery can be applied to reduce pain perception and improve patient comfort. This study aimed to determine the effect of guided imagery on changes in pain levels among post-abdominal surgery patients in the Plamboyan Ward of RSUD Praya, Central Lombok Regency. A pre-experimental study with a one-group pretest–posttest design was conducted involving 30 respondents selected through purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the guided imagery intervention, which was administered for approximately 10–15 minutes in a calm and comfortable setting. Data analysis was performed using a paired t-test with a significance level of 0.05. The results demonstrated a decrease in the mean pain score after the intervention compared to before the intervention, and statistical analysis showed a significant difference in pain levels before and after guided imagery (p < 0.05). These findings indicate that guided imagery has a significant effect on reducing postoperative pain in patients undergoing abdominal surgery and can be considered an effective independent nursing intervention to support postoperative pain management and enhance patient comfort.